Human Error Quantification Models applied in the Modern Manufacturing Industry - Salas-Arias, Karla Melissa (2017)
This document proposes a review of the use of different methods considered of potential use for the assessment of human reliability in areas of risk greatest. The Human Reliability Analysis (HRA)is to identify and characterize aspects that cause an error in task where have being the human intervention.The application of models to analyze the man-machine relationship focused on the human factor, in modern manufacturing, aims to improve productivity of operations. In this review twelve techniques were identified with increased use in industrial scale which is referenced each.